Communicating about Health : current issues and perspectives - Pre, Athena du. (New York : Oxford University Press, 2010)
"Now in its fifth edition, Communicating About Health: Current Issues and Perspectives continues to live up to its long-standing reputation as the most dynamic and current exploration of health communication on the market. The book offers rich, current research and in-depth analysis of the cultural, social, and organizational issues that influence health communication and health advocacy. Communicating About Health is an indispensable resource for readers seeking to improve their communication abilities in fields related to health. This text explores health communication through the eyes of patients, care providers, health care leaders, campaign designers, and more. Readers will learn how culture, media, personal identity, technology, social networks, and other factors contribute to health and healing"--
Establishing a context for health communication -- The roles of patients and professional caregivers -- Sociocultural issues -- Coping and health resources -- Communication in health organizations -- Media, public policy, and health promotion.
Includes bibliographical references (p. R-1-R-66) and indexes (p. I-1-I-20).
Keywords: Communication in medicine; Medical personnel and patient; Health education; Health promotion